Measuring Hemoglobin Levels in the Optic Disc of Parkinson’s Disease Patients Using New Colorimetric Analysis Software - Maria Pilar Bambo; Elena Garcia-Martin; Maria Satue; Susana Perez-Olivan; Silvia Alayon; Marta Gonzalez-Hernandez; Vicente Polo; Jose Manuel Larrosa; Manuel Gonzalez-De la Rosa (Parkinson's Disease)
Objective. To evaluate a new method of measuring hemoglobin (Hb) levels and quantifying the color changes in the optic nerve head of Parkinson’s disease (PD) patients. We also compared differences in retinal nerve fiber layer (RNFL) thicknesses obtained using spectral domain optical coherence tomography (OCT) device between PD group and healthy group. Methods. One hundred and fifty-five PD patients and 91 sex- and age-matched healthy subjects were included in this cross-sectional study. OCT examinations and one photograph of the optic disc were performed. The Laguna ONhE (“optic nerve hemoglobin”; Insoft SL, Tenerife, Spain) software was used to analyze the Hb level on the acquired optic disc photographs. Results. PD patients exhibited significantly reduced mean optic disc Hb percentages (57.56% in PD, 67.63% in healthy subjects; P=0.001) as well as reduced Hb in almost all analyzed sectors, with the largest differences detected in the inferior and nasal sectors. RNFL parameters were significantly reduced in PD patients compared with healthy subjects, especially in the inferior quadrant. Conclusions. Measurements of optic disc Hb levels obtained with the Laguna ONhE software had good ability to detect optic nerve color changes (more papillary paleness and consequently this could suggest optic atrophy and axonal loss) in PD patients.